2017
DOI: 10.1027/0227-5910/a000447
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Plans and Attempts Among Adolescents in Mongolia

Abstract: Given the comparable patterns of risk between urban and rural adolescents and the relatively high rates of suicidal plans and attempts, similar mental health services and interventions are necessitated for both urban and rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
(54 reference statements)
3
17
4
1
Order By: Relevance
“…[10,26]. Some research [9,11,27] showed an association between sexual behaviour, injury, soft drink intake and suicide attempt, while this study did not discover such links.…”
Section: Discussioncontrasting
confidence: 67%
“…[10,26]. Some research [9,11,27] showed an association between sexual behaviour, injury, soft drink intake and suicide attempt, while this study did not discover such links.…”
Section: Discussioncontrasting
confidence: 67%
“…A positive association was also reported after adjustment for confounders in several cross-sectional studies. Davaasambuu et al reported a 31% increased odds of suicide attempt in multivariable analysis (aOR 1.31, 95% confidence interval 1.03–1.67) [ 48 ]. Pillai et al detected a strong relationship between missing four or more days of school in 3 months and a suicide attempt during the same period in Goa (India), but this relationship did not hold for lower levels of absence.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariable results from seven cross-sectional studies met criteria for combination in a meta-analysis [ 46 , 48 , 52 , 55 , 63 , 64 , 69 ] to provide a combined sample size of 88,922 ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The large and growing burden of mental health and substance use disorders among older children and adolescents also is an emerging threat to the thrive component of the SDG survive and thrive agenda. While the psychological needs of children and adolescents show similarities across geographical settings, 24 , 25 , 26 , 27 comparatively little is understood about modifiable risk factors or effective prevention programs for childhood mental illness, outside of ensuring that caregivers are attuned to the link between mental health disorders and self-harm. 28 , 29 Injuries in general continue to be a major cause of early mortality and long-term disability among older children and adolescents in all countries.…”
Section: Discussionmentioning
confidence: 99%